Spam Detection Approach Using Modified Pre-processing With NLP - Choudhary, Neelam; Dubey, Nitesh (International Journal of Computer Sciences and Engineering, 2025)
However, the growth in emails has also led to an unprecedented increase in the number of illegitimate mail, or spam 49.7% of emails sent is spam - because current spam detection methods lack an accurate spam classifier. We are excited by the decline in the volume of email spam but it also raises the question as to whether the email spam business is dying and will continue to decline. Besides the volume change, we also consider the quality of email spam and the impact, which may constitute a new trend of email spam business. For instance, spammers may post email spam in a more complicated way using spoofed email addresses and changing email relay servers. That kind of email spam may slip away under the inspection of spam filters. Thus, it motivated us to investigate the evolution of email spam using advanced techniques such as topic modelling and network analysis. We try to find out the real trend of email spam business through email content, meta information such as headers, and sender-to-receiver network over a long period of time.